Interpretation of mass spectra - Mclafferty, F.w. ([S.l.] : Univ Science Books, 1980)
Extensively revised and updated, this new edition, as in previous editions, emphasizes the point that the most important part of learning how to interpret unknown mass spectra is to practice interpreting mass spectra. The book aims at correlating ion dissociation mecanisms on a much broader scale, with the emphasis on basic attributes such as ionization energies, proton affinities and bond dissociation energies. The authors also tried to show how these mechanisms are applicable to the unimolecular dissociations of ions formed by any ionization method, including the new methods for obtaining mass spectra of large molecules.